2006
DOI: 10.1002/app.24644
|View full text |Cite
|
Sign up to set email alerts
|

Effect of octene content in poly(ethylene‐co‐1‐octene) on the properties of poly(propylene)/poly(ethylene‐co‐1‐octene) blends

Abstract: Ethylene-octene random copolymer (EOC) is one of the most commonly employed elastomers for PP, and as such its rubber toughening efficiency has been extensively studied. However, most existing studies employ EOC containing an octene comonomer of about 8 mol %. Therefore, in this study, we investigated the effect of EOC octene comonomer content on the morphology and thermal and mechanical properties of PP-ethylene random copolymer (PP-CP)/EOC (80/20 wt %/wt %) blends. It was clearly shown that the properties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Copolymers with more than 20 wt% of octene are elastomeric and due to the chemical similarity and easy processability can be widely used to toughen polyolefin polymers [17] . There is evidence in the literature that the comonomer content of the metallocene ethylene-α -olefin copolymers has a strong effect on the properties of high impact polypropylene/LDPE blends and on the properties of polypropylene-ethylene random copolymer / EOCs blends [18] . The grades of EOCs used in this work present the same MFI values and different comonomer content (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Copolymers with more than 20 wt% of octene are elastomeric and due to the chemical similarity and easy processability can be widely used to toughen polyolefin polymers [17] . There is evidence in the literature that the comonomer content of the metallocene ethylene-α -olefin copolymers has a strong effect on the properties of high impact polypropylene/LDPE blends and on the properties of polypropylene-ethylene random copolymer / EOCs blends [18] . The grades of EOCs used in this work present the same MFI values and different comonomer content (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Lee et al [18] verified in a study of polypropyleneethylene random copolymer (PP-CP) and EOC blends that the rubber particle size decreased as the octene content in the ethylene-α-olefin random copolymer increased. As the rheological properties of all EOCs and PP-CP/ EOC blends were identical, they inferred that interfacial interaction between PP-CP and EOCs increases as the octene content in EOC increases.…”
Section: Rocha Mcg Et Al -Thermoplastic Elastomers Blends Based mentioning
confidence: 99%
“…Addition of an elastomer, especially metallocene or single‐site catalyzed ethylene‐co‐octene copolymers (EOR), can lead to an improvement in the toughness of poly(propylene) (PP); however, the presence of the elastomer also reduces stiffness and increases CTE . In our previous article, we have shown that PP can be toughened with the elastomer using an organoclay to control elastomer particle size; these extruder‐made TPO nanocomposites can have a good balance of toughness and stiffness .…”
Section: Introductionmentioning
confidence: 99%
“…Polypropylene (PP) and organoclay based nanocomposites containing maleated polypropylene have shown significant improvement in the mechanical properties and decreased thermal expansion 2–7. PP toughened with an elastomer, especially metallocene or single‐site catalyzed ethylene‐ co ‐octene copolymers (EOR), leads to an improvement in the toughness; however, the presence of the elastomer reduces the stiffness of the blend 8–35. Blends of PP and elastomer are generally referred to as “thermoplastic olefin” or TPO.…”
Section: Introductionmentioning
confidence: 99%